2009
DOI: 10.4152/pea.200905599
|View full text |Cite
|
Sign up to set email alerts
|

New Mechanism Synthesis of 1,4-Benzothiazine and its Inhibition Performance on Mild Steel in Hydrochloric Acid

Abstract: Abstract1-(3-methyl-4H-1,4-benzothiazin-2-yl)ethanone (1,4-BT) was synthesised via a new mechanism. 1,4-BT was thereafter tested as corrosion inhibitor of mild steel in hydrochloric solution at 293 K by weight loss measurements and electrochemical techniques (potentiodynamic polarisation, polarisation resistance, impedance spectroscopy (EIS)). Inhibiting efficiency (E%) increased with concentration and reached highest values up to 98% even at low concentration with changing the mechanism of the corrosion proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…Special attention was paid to the effect of electron donating on the atom, electron withdrawing or groups responsible for adsorption and hence on the inhibitor performance. Furthermore, it has been observed that the adsorption mainly depends on steric factors, aromaticity, the structural properties of the organic compounds studied such as the presence of p-electrons and heteroatoms, which induce greater adsorption of the inhibitor molecules onto the surface of C38 steel [7][8][9]. The effect of temperature on the corrosion behaviour was also studied in the range of temperature from 313 to 353 K. Kinetic and activation parameters that govern metal corrosion have been evaluated and discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Special attention was paid to the effect of electron donating on the atom, electron withdrawing or groups responsible for adsorption and hence on the inhibitor performance. Furthermore, it has been observed that the adsorption mainly depends on steric factors, aromaticity, the structural properties of the organic compounds studied such as the presence of p-electrons and heteroatoms, which induce greater adsorption of the inhibitor molecules onto the surface of C38 steel [7][8][9]. The effect of temperature on the corrosion behaviour was also studied in the range of temperature from 313 to 353 K. Kinetic and activation parameters that govern metal corrosion have been evaluated and discussed.…”
Section: Introductionmentioning
confidence: 99%
“…The principal type of interaction between an organic inhibitor and metal surface is physisorption or chemisorption or both. The adsorption of inhibitor is influenced by the nature of the metal, chemical structure of inhibitors, type of aggressive electrolyte, temperature and the morphology of MS [53,54]. The values of inhibition efficiency depend essentially on the electron density at the active centre of the inhibitor molecule.…”
Section: Mechanism Of Inhibitionmentioning
confidence: 99%
“…One of the methods employed for the preparation 1,4-benzothiazines involves nucleophilic substitution of disulfide by β-keto esters and 1,3-diketons in presence base [9]. Recently Forsal et al [10] also have reported that condensation of 2-amino thiophenol with acetylacetone in boiling ethanol afforded 60% yield of 1,4-BT derivative 3and trace of a yellow crystal of 2,2'disulfanediyldianiline 4 (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…When the reaction is carried according to this method and under the same reaction conditions reported in Literature [10], the 1-(3-methyl-4H-benzo[b] [1,4]thiazin-2-yl)ethanone 2 is not isolated. In our hand, we isolate 1-( 2-methyl -2,3 -dihydrobenzo [d] thiazol -2-yl) propan -2-one 3 from the reaction of 1 with acetyl acetone in refluxing ethanol in an excellent yield.…”
Section: Organic and Medicinal Chemistry International Journalmentioning
confidence: 99%